SISTEM INFORMASI GURU DI SEKOLAH DASAR - Nopredi, Basrul; Jasrial, Jasrial (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
The development of information technology nowadays is developing and advancing rapidly. Schools must look for other alternatives in dealing with problems faced by schools. One of the things that can be done by school is to use an information system in its managerial. Information system at SD Negeri 22 Alai using the Students’ Data application. Students’ Data is a data collection system and management of micro educational data online and real time. There are several main types of data managed in the Students’ Data system, including school data, educator data, employee data, and school staff data. Information systems that are operated are very helpful for principals or leaders in taking policies and evaluating policies and other managerial tasks.